Ethnobotanical study of medicinal plants used by the Tuwalis of Ifugao, Cordillera Administrative Region, Philippines - Galvez, Marie Ann C. (Plant Science Today, 2024)
Indigenous groups have used the ethnomedicinal plants in the country as part of their healthcare, but no record was found among the Tuwalis of Lamut, Ifugao, Philippines. Thus, this study aims at documenting their ethnomedicinal knowledge. Semi-structured interviews were utilized to obtain the data from twenty informants, which were then evaluated by some quantitative indices for analysis, including the relative frequency of citation (RFC), use value (UV), relative importance (RI), fidelity level (FL), and informant consensus factor (ICF). There were 87 plant species recorded, represented by 47 families, with the majority belonging to the Asteraceae family (9 species). The most prevalent plant part utilized for healing was the leaves (30%). These plants treated 54 diseases and conditions, where the most typical medicinal use was for cough (13.59%) and diarrhoea (6.62%). The most typical preparation method was decoction, and drinking was the most commonly used mode of administration. Moringa oleifera (0.60) and Ananas comosus (0.50) had the highest RFC values. Annona muricata (1.0) had the highest UV value, while Diplazium esculentum and M. oleifera had the highest RI value of 0.88. The plant species mostly used with a 100% fidelity level were Carica papaya, Psidium guajava, Senna alata, and Momordica charantia. Diseases of the endocrine system (0.60) have the greatest ICF value. These results could aid possible pharmaceutical studies and will help emphasize the value of preserving biodiversity and traditional knowledge.